Out of School and Out of Work : Risk and Opportunities for Latin America’s Ninis - de Hoyos, Rafael; Rogers, Halsey; Székely, Miguel (World Bank, Washington, DC, 2015)
One in five youth aged 15 to 24 in Latin America is out of school and not working (ninis). Nearly 60 percent of ninis in the region are from poor or vulnerable households in the bottom 40 percent of the income distribution, and 66 percent are women. At the same time, it is men who account for the growth in 2 million ninis during the last 20 years. The study undertakes a comprehensive diagnosis quantifying the problem, develops a conceptual framework identifying the determinants of youths' choices, uses all the available data to test the theoretical implications, and reviews the evidence regarding interventions that have proven effective in keeping youth in school and helping them become employed. The findings of the study offer policy makers in the region with options to provide opportunities to the region's 20 million ninis.